2009
DOI: 10.1292/jvms.71.1049
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Prevention Efficacy against Mosquito Bloodsucking and Dirofilaria immitis Infection by Administration of Topical Insecticide

Abstract: Inhibition and prevention of mosquito bloodsucking by a topical insecticide, and the consequent infection of Dirofilaria immitis were evaluated using a product containing 10% w/w imidacloprid plus 50% w/w permethrin (I-P solution). Nine healthy beagle dogs divided in three groups of 3 dogs each were administered I-P solution on day 3 (group 1), day 36 (group 2) and not administered (group 3 as a control) before starting the experimental infection. The results showed that the mosquito bloodsucking rate was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In addition, this approach includes vector mosquito control using conventional methods such as insecticide application, biological control, drainage of standing water and direct treatment of animals, particularly dogs, by topical application of repellent ectoparasiticides to repel and kill infected or uninfected adult mosquitoes before biting and transmission of mf to mosquitoes or L 3 to dogs occur [21,22]. For some time, it has been known that topical administration of insecticides is effective in reducing vector mosquito populations [25][26][27][28][29][30][31][32][33][34][35][36]. It has only recently been shown that oral administration of some isoxazalines has a similar effect [23] (in this issue) [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this approach includes vector mosquito control using conventional methods such as insecticide application, biological control, drainage of standing water and direct treatment of animals, particularly dogs, by topical application of repellent ectoparasiticides to repel and kill infected or uninfected adult mosquitoes before biting and transmission of mf to mosquitoes or L 3 to dogs occur [21,22]. For some time, it has been known that topical administration of insecticides is effective in reducing vector mosquito populations [25][26][27][28][29][30][31][32][33][34][35][36]. It has only recently been shown that oral administration of some isoxazalines has a similar effect [23] (in this issue) [24].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the influence of a topical repellent (imidacloprid-permethrin, IP) in the prevention of heartworm transmission has been assessed previously only once [ 15 ]. In that experiment, however, the methodology was completely different: there were three dogs per group compared with eight in the present study, the experimental infection of the control untreated dogs (1–4 worms/dog) was lower than the threshold required by FDA (≥5 worms/dog), and the animals were treated with the product 3 or 36 days prior to exposure to D. immitis -infected mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported varying levels of success with the use of topically applied products for repelling and/or killing several different species of mosquitoes [ 11 – 13 ]. One study assessed the infection of dogs and cats by West Nile virus– infected mosquitoes [ 14 ], but only one of these studies included mosquitoes or animals infected with D. immitis [ 15 ]. Encouraged by the high level of effectiveness of one of these products (Vectra® 3D, dinotefuran-permethrin-pyriproxyfen, DPP; Ceva Animal Health) against Aedes aegypti [ 16 ] and Culex pipiens [ 17 ], we investigated the role of DPP in blocking heartworm parasite transmission in dogs in two studies.…”
Section: Introductionmentioning
confidence: 99%
“…Fighting these diseases takes many efforts including pesticide research, vaccine development, and mosquito control (N'Guessan et al 2010;Hayasaki and Saeki 2009;Bonin et al 2009;Jambulingam et al 2008). Insecticides play a central role in controlling mosquitoes.…”
Section: Introductionmentioning
confidence: 99%